A Novel Striated Muscle-Specific Myosin-Blocking Drug for the Study of Neuromuscular Physiology - Heredia, Dante J.; Schubert, Douglas; Maligireddy, Siddhardha; Hennig, Grant W.; Gould, Thomas W. (Frontiers in Cellular Neuroscience, 2016)
The failure to transmit neural action potentials (APs) into muscle APs is referred to as neuromuscular transmission failure (NTF). Although synaptic dysfunction occurs in a variety of neuromuscular diseases and impaired neurotransmission contributes to muscle fatigue, direct evaluation of neurotransmission by measurement of successfully transduced muscle APs is difficult due to the subsequent movements produced by muscle. Moreover, the voltage-gated sodium channel inhibitor used to study neurotransmitter release at the adult neuromuscular junction is ineffective in embryonic tissue, making it nearly impossible to precisely measure any aspect of neurotransmission in embryonic lethal mouse mutants. In this study we utilized 3-(N-butylethanimidoyl)-4-hydroxy-2H-chromen-2-one (BHC), previously identified in a small-molecule screen of skeletal muscle myosin inhibitors, to suppress movements without affecting membrane currents. In contrast to previously characterized drugs from this screen such as BTS, which inhibit skeletal muscle myosin ATPase activity but also block neurotransmission, BHC selectively blocked nerve-evoked muscle contraction without affecting neurotransmitter release. This feature allowed a detailed characterization of neurotransmission in both embryonic and adult mice. In the presence of BHC, neural APs produced by tonic stimulation of the phrenic nerve at rates up to 20 Hz were successfully transmitted into muscle APs. At higher rates of phrenic nerve stimulation, NTF was observed. NTF was intermittent and characterized by successful muscle APs following failed ones, with the percentage of successfully transmitted muscle APs diminishing over time. Nerve stimulation rates that failed to produce NTF in the presence of BHC similarly failed to produce a loss of peak muscle fiber shortening, which was examined using a novel optical method of muscle fatigue, or a loss of peak cytosolic calcium transient intensity, examined in whole populations of muscle cells expressing the genetically-encoded calcium indicator GCaMP3. Most importantly, BHC allowed for the first time a detailed analysis of synaptic transmission, calcium signaling and fatigue in embryonic mice, such as in Vamp2 mutants reported here, that die before or at birth. Together, these studies illustrate the wide utility of BHC in allowing stable measurements of neuromuscular function.